Biogeochemical cycling of sulfur, manganese and iron in ferruginous limnic analog of Archean ocean. (1st March 2021) - Boyko, Valeria; Avetisyan, Khoren; Findlay, Alyssa; Guo, Qingjun; Yang, Xi; Pellerin, André; Kamyshny, Alexey
Abstract: The early evolution of life on Earth was intimately coupled with the evolution of ocean chemical composition and redox conditions in Archean ocean. However, the measurements of chemical and isotopic compositions of Archean sedimentary rocks does not provide sufficient information for understanding the biogeochemical processes that characterized oceans during this period. In this research, the cycling of the redox-sensitive elements in the water column and sediments of the seasonally stratified Lake Sihailongwan, China, was studied. It was found that during the stratification, the concentrations of sulfate ions in the epilimnion were <100 μmol L −1 . The hypolimnion of the lake becomes anoxic and contains iron, manganese and low concentrations of hydrogen sulfide. These conditions are similar to those suggested to exist in the Archean ocean, and therefore the biogeochemical cycles in Lake Sihailongwan may be analogous to those in the Archean ocean. In Lake Sihailongwan, the chemocline is always deeper than the thermocline. The hypolimnion is supersaturated with respect to iron sulfide in August, while in May and October, this supersaturation is present only in the lower hypolimnion. The concentration profiles of the redox species in the water column and in the sediments show that dissolved iron(II) and manganese(II) diffuse from the sediments into the water column, while hydrogen sulfide and sulfate diffuse into the sediment. At the hypolimnion, the sulfur isotope fractionation values are consistent with microbial sulfate reduction, possibly combined, to a minor extent, with disproportionation of zero-valent sulfur. The absolute sulfur isotope fractionation factor increases between spring and autumn and decreases with water depth, possibly due to precipitation of iron sulfide in the lower hypolimnion. The fraction of highly reactive iron in the sediments is mainly composed of iron(II) carbonates and the most reactive iron(III) (hydr)oxide phases. Iron-based redox proxies are consistent with sediment deposition under ferruginous water column conditions. In the sediment, concentrations of sulfate and hydrogen sulfide are low, and sulfur isotope composition of sedimentary pyrite is equal to that of the epilimnetic sulfate. The obtained results demonstrated that despite a low sulfate concentration in the water column, sulfur isotope fractionation is high. However, due to the complete consumption of the sulfate reservoir, the large isotope fractionation is not preserved in the sedimentary record.